Cerium anomalies and iodine track nonuniform paleoredox conditions during the Aptian Oceanic Anoxic Event 1a - Arman Jafarian; Antun Husinec; Ardiansyah Koeshidayatullah; Xi Chen; Meng Wang; Clemens Vinzenz Ullmann; Abdus Saboor; Kaibo Han; Chengshan Wang (Scientific Reports)
Abstract The Early Aptian Oceanic Anoxic Event 1a (OAE 1a) marks a period of global marine anoxia linked to volcanic activity and climate changes during the Cretaceous. This study analyzes a ~ 40-m-thick Lower Aptian succession from the Kazhdumi Intrashelf Basin, Iran, using I/(Ca + Mg) ratios, Ce anomalies, trace elements, δ¹³C, and REY parameters. Results reveal persistent suboxic to anoxic bottom-water conditions, with increased oxygenation in segments C3 and upper C5 + C6, driven by weathering and sea-level changes. Minimal diagenetic overprinting is indicated by C-isotope trends and low Mn/Sr ratios. The Kazhdumi Basin serves as a high-resolution archive of redox evolution during OAE 1a, emphasizing the utility of I/(Ca + Mg) and Ce anomalies as proxies in ancient carbonates.